ACCRETION INTO BLACK HOLES WITH MAGNETIC FIELDS, AND RELATIVISTIC JETS - Bisnovatyi-Kogan, G. S.; Klepnev, A. S.; Lovelace, R. V.E. (Одеські астрономічні публікації, 2011)
We discuss the problem of the formation of a large-scale magnetic field in the accretion disks around black holes, taking into account the non-uniform vertical structure of the disk. The high electrical conductivity of the outer layers of the disk prevents the outward diffusion of the magnetic field. This implies a stationary state with a strong magnetic field in the inner parts of the accretion disk close to the black hole, and zero radial velocity at the surface of the disk. Structure of advective accretion disks is investigated, and conditions for formation of optically thin regions in central parts of the accretion disk are found. The problem of jet collimation by magneto-torsion oscillations is considered.